IMPROVING THE QUALITY OF LEARNING THROUGH LIFESKILL ACTIVITIES AT MUHAMADIYAH AHMAD DAHLAN AEKKANOPAN JUNIOR HIGH SCHOOL - Silvia Febrianti; Salmiah Salmiah; Safira Achmad Pane; Mavianti Mavianti (Proceeding International Seminar of Islamic Studies, 2022)
Quality of learning is the quality or excellence of the learning process carried out in the teaching and learning process. The quality of learning is one of the most important things in teaching and learning activities that must be achieved by an educator. Educators themselves are people who provide knowledge and new knowledge for others consistently and continuously. The formulation of the problem related to this research is to increase the quality of student learning through life skills activities at Muhammadiyah Junior High School Ahmad Dahlan Aekkanopan. While the purpose of this study is to analyze activities that can improve the quality of student learning. In this article, the method used is a qualitative description method in the form of interviews and observations of teachers and students of grade 9 Muhammadiyah Middle School Ahmad Dahlan Aekkanopan. Based on the results of interviews and observations, it can be concluded that life skills activities can improve the quality of student learning, this can be seen from students who have polite, courageous, creative, independent attitudes, are able to manage time and are enthusiastic in participating in all learning activities that are supported by excellent school programs.Keywords: Quality of Learning, Educators, Lifeskill